ANALISIS KETERAMPILAN PRIBADI ROOM ATTENDANT UNTUK MENINGKATKAN KEPUASAN PENGUNJUNG THE GOLDEN BAY HOTEL BATAM - Ridho As Shiddiqi; Supardi; Arina Luthfini Lubis (JURNAL MEKAR, 2023)
The Golden Bay Hotel Batam is a four-star quality hotel, with world standards, located on  Bengkong Laut Gold City in Batam. The hotel provides well-designed and comfortable rooms with wooden floors and city views, as well as a variety of additional facilities and activities to make visitors' stay more enjoyable. The cleaners are always impressed with the cleanliness of The Golden Bay Batam Hotel. This section is responsible for keeping the entire hotel environment clean, nice and tidy both inside and outside. Service presence, followed by friendliness and seamlessly provided facilities, drives a sense of satisfaction among guests, so that they come back for more. Soft skills, play an important role in the workplace as they are internal qualities that people have. Several concerns have been raised by visitors in tripadvisor comments, including displeasure with the performance of the room attendants. Some of the visitors' complaints on TripAdvisor are about unpleasant workers, sluggish service, and problems with accommodation. Based on the conclusions from the data obtained from interviews with three respondents about the soft skills of room attendants at The Golden Bay Hotel Batam, communication soft skills are the most important requirement. Meanwhile, compared to communication soft skills, emotional soft skills and critical thinking are the least needed. Because not all room attendants pay attention to visitors while carrying out their duties, guests complain. Room attendants should pay more attention to how important client preferences are at The Golden Bay Hotel Batam to increase visitor satisfaction. Room staff must also be aware of work support equipment that is no longer suitable for its purpose and must be updated so that it does not damage itself. To communicate with foreign tourists, flight attendants must master many languages. Communication indicators have developed into soft skills that play an important role in increasing visitor satisfaction.